2021
DOI: 10.3390/environments8090094
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Rhizobacterium Rhodobacter sphaeroides KE149 and Biochar on Waterlogging Stress Tolerance in Glycine max L.

Abstract: In the context of the current climate change and increasing population scenarios, waterlogging stress in plants represents a global threat to sustainable agriculture production. Plant-growth-promoting rhizobacteria and biochar have been widely reported to mitigate the effects of several abiotic stresses. Hence, in the present study, we examined the effect of the rhizobacterium Rhodobacter sphaeroides KE149 and biochar on soybean plants subjected to sufficient water supply and waterlogging stress conditions. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…It is also known as a "stress hormone" that controls numerous responses to abiotic stresses, but its role in flood tolerance leftovers many gaps (Zhao et al, 2021). Hormonal application is a well-known agronomic approach to mitigating the toxic effects of flood stress in soybean (Kang et al, 2021;Pan et al, 2021;Tamang et al, 2021;Wang and Komatsu, 2022). Tamang et al (2021) revealed that abscisic (ABA) acid and ethylene (ET) are candidate hormones that direct transcriptomic energy-saving developments under flood stress.…”
Section: Role Of Growth Hormones In Flood Tolerancementioning
confidence: 99%
“…It is also known as a "stress hormone" that controls numerous responses to abiotic stresses, but its role in flood tolerance leftovers many gaps (Zhao et al, 2021). Hormonal application is a well-known agronomic approach to mitigating the toxic effects of flood stress in soybean (Kang et al, 2021;Pan et al, 2021;Tamang et al, 2021;Wang and Komatsu, 2022). Tamang et al (2021) revealed that abscisic (ABA) acid and ethylene (ET) are candidate hormones that direct transcriptomic energy-saving developments under flood stress.…”
Section: Role Of Growth Hormones In Flood Tolerancementioning
confidence: 99%
“…There are also studies exploring the interaction between phototrophic bacteria and plants, such as their ability to produce plant-growth-promoting substances [ 49 ]. The main contributions of phototrophic bacteria to plants include aiding in nitrogen fixation, solubilizing phosphate, and increasing the content of soluble sugars and secondary metabolites [ 50 , 51 , 52 ]. Additional plant-growth-promoting mechanisms of PNSB can be explored in the comprehensive review [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a IAA-producing rhizobacterium R. sphaeroides KE149 was reported to be able to improve adzuki bean's morphological characteristics as well as to regulate phytohormone content under flood and drought stress [78]. In addition, co-inoculation with KE149 and biochar could help to promote plant growth and strengthen the antioxidant system of soybean plant while grown under normal and stress conditions [79].…”
Section: Plant Growth Promoting (Pgp) Traits Exerted By Pnsb On Cropsmentioning
confidence: 99%
“…PNSB has also shown the potential to enhance the contents of a variety of secondary metabolites in crops [53,79]. For example, R. palustris KL9 was reported to enhance the lycopene content in harvested tomato fruits.…”
Section: Pnsb Inoculants Can Improve the Quality And Nutritional Value Of Food Cropsmentioning
confidence: 99%
See 1 more Smart Citation